Research on the Safety and Stability Evaluation for a New Type of Prefabricated Aqueduct in the Construction Stage - Yamin Li; Lingyu Zhou; Wei Huang; Jinheng Li; Manjun Liao; Hongyuan Wei; Jiaopeng Fang (Buildings)
To address the issue of regional water resource scarcity, water diversion projects have been constructed worldwide. As an essential lifeline project, the prefabricated aqueduct is prevalently utilized in cross-regional water transfer and diversion projects. This paper was based on the prefabricated aqueduct project, which adopted fabricated technologies including the connection technology among the gravity pier, the prefabricated arch ribs, and the prefabricated bent frame columns. The PHC piles, bearing platforms, bent frame columns, arch ribs, and groove bodies were all prefabricated components that were transported to the site for installation. The connections of the prefabricated aqueduct employed to link different components were of such crucial significance that their safety and stability determined whether the overall structure would be compromised. Therefore, the main objective of this paper was to examine the stress and deformation of this prefabricated aqueduct to prevent the occurrence of security risks throughout the entire construction stage. The finite element model was established in Midas Civil, and the entire construction stage was simulated and analyzed. Coupled with on-site monitoring, the stress and deformation of the prefabricated aqueduct were evaluated. The results indicated that the tensile stress, the compressive stress, the vertical displacement, and the lateral displacement of each part of the prefabricated aqueduct met the requirements of the standard, suggesting that the overall structure with the applied connection technology was in a safe and stable state throughout the entire construction stage.